A imprensa como instância educativa em Mariana, Minas Gerais na primeira metade dos Oitocentos: estratégias da escrita. - Priscilla Samantha Barbosa Verona (2020)
The research sought to investigate the forms and writing strategies that were used by the newspaper during the first half of the eight hundred to educate its readers in the province of Minas Gerais. The main source used for the research is the first political journal to be printed in the city of Mariana, entitled Estrella Mariannense (1830-1832). In addition to this, the other periodicals printed in Typografia Mariannense at the same time, all of them belonging to the Acervo do Arquivo Nacional, were also analyzed as an auxiliary source, and some other contemporary Minas Gerais newspapers. Atas da Câmara de Mariana found in Arquivo Histórico da Câmara Municipal de Mariana (ICHS/UFOP), Manuais de Retórica that were located at the Biblioteca Nacional de Portugal, and Listas Nominativas (Cedeplar) also served as an auxiliary source. Considering the educational pretensions of the press, the research aimed to analyze which strategies were constructed and implemented, through text and materiality, to convince readers about the importance of liberalism's assumptions in the process of building a Nation. From the reflections that come from the Cultural History and the dialogue with the history of the book and the reading, we seek to make an analysis of the newspaper that contemplates aspects of its production, circulation, and reception, thus understanding both the text and its materiality. We understand, therefore, that the writing of the Marianense press was not only used to convey and debate politics, but was configured as an educational strategy. Thinking the print from the point of view of its production and circulation, we identified that its composition movement, which was the result of the compilation of countless other texts, was also strategic because it was based on a repertoire of authority that gave legitimacy to the text conveyed by the newspaper. In tracing the main bases of argument supported by the newspaper we identified that the discursive, rhetorical and typographic elements present in the writing became fundamental for the meanings assumed by the print and were embodied in strategies to convince the readers and under the presuppositions of liberalism.